Tocilizumab in Systemic Juvenile Idiopathic Arthritis: Response Differs by Disease Duration at Medication Initiation and by Phenotype of Disease - Yan, Xin; Tang, Wenjing; Zhang, Zhiyong; Zhang, Yu; Luo, Chong; Tang, Xuemei (Frontiers in Pediatrics, 2021)
Objective: We performed a single-center retrospective study to determine the different efficacy of tocilizumab (TCZ) in the early and late stages and in three phenotypic subgroups (monocyclic, polycyclic, and persistent) of systemic juvenile idiopathic arthritis (sJIA). Methods: Clinical and serological parameters of 77 sJIA patients treated by TCZ were collected from November 1, 2013 to May 1, 2019. Patients were grouped based on the duration group A < 6 months (n = 41) and group B > 6 months (n = 36) and divided into three phenotypes: monocyclic (n = 12), polycyclic (n = 14), and persistent (n = 51) course. Results: At baseline, group A had pronounced ESR, fever less active arthritis than group B (p < 0.05). After 12 weeks of therapy, TCZ alleviated fever, ESR, CRP, and systemic-onset juvenile arthritis disease activity score-27 (sJADAS27) in both group A and group B (p>0.05), while the efficacy of TCZ in relieving active arthritis in group A was better than that in group B (p<0.05). After 1 year of TCZ therapy, it showed that patients with monocyclic phenotype had the highest clinical response rate (91.7%, odds ratio = 0, 95% CI: 24–24, p = 0.00), followed by the polycyclic (28.6%, odds ratio = 2.1, 95% CI: 10.5–18.8, p = 0.00) and the persistent course (9.8%, odds ratio = 1.2, 95% CI: 9.5–13.8, p = 0.00). Conclusion: TCZ can quickly relieve fever and inflammation, especially when patients have less active arthritis with shorter disease duration. The long-term efficacy of TCZ is related to the phenotypes, among which the monocyclic is the best, and the persistent is the worst.